2015
DOI: 10.1111/ajr.12251
|View full text |Cite
|
Sign up to set email alerts
|

Losing the rural nursing workforce: Lessons learnt from resigning nurses

Abstract: To facilitate nurse retention, it is important that rural hospitals manage nurse resignations more effectively. This includes re-examining resignation procedures, how nurses are treated and collecting meaningful data to inform retention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Our findings support the feasibility and acceptability of the PFPI and indicate benefits in improving patients' BP control, dyadic relationship and psychological well‐being of the family dyads in rural area. Recent studies have demonstrated that shortage of health workforce and limited health care resources are common in rural areas in both developing and developed countries, such as China 33 and Australia, 34 respectively, which can impede the implementation of conventional evidence‐based hypertension management programs. The findings of this study suggest that a family‐oriented approach of integrating patient‐family carer partnership into current hypertension care intervention would be a more feasible and effective approach to hypertension management in the rural areas where health professionals' support is inadequate and regular visits to the needy residents with hypertension might not be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support the feasibility and acceptability of the PFPI and indicate benefits in improving patients' BP control, dyadic relationship and psychological well‐being of the family dyads in rural area. Recent studies have demonstrated that shortage of health workforce and limited health care resources are common in rural areas in both developing and developed countries, such as China 33 and Australia, 34 respectively, which can impede the implementation of conventional evidence‐based hypertension management programs. The findings of this study suggest that a family‐oriented approach of integrating patient‐family carer partnership into current hypertension care intervention would be a more feasible and effective approach to hypertension management in the rural areas where health professionals' support is inadequate and regular visits to the needy residents with hypertension might not be possible.…”
Section: Discussionmentioning
confidence: 99%
“…In its policy analysis on nurse retention, the International Centre on Nurse Migration (Buchan et al 2018) recommended that exit interviews should be conducted and that retention strategies should be developed based on the data obtained from these interviews. However, nurses may not always express the real reasons for leaving since exit interviews are conducted by organizational managers (Bragg & Bonner 2015). Therefore, in this study, data were collected by researchers not affliated with the organization of nurses who decided to leave their job.…”
Section: Introductionmentioning
confidence: 99%
“…• The results of this research highlight a lack of organisational commitment to employees, which has a negative impact on the well-being of nurses and patient safety in rural and remote communities. low staff morale and possible negative impacts on patient care and satisfaction (Bragg & Bonner, 2015;Buykx et al, 2010). Research has identified several key issues causing nurses to leave, including a lack of professional development opportunities, lack of support, high workloads, minimal infrastructure, isolation, working beyond their scope of practice and community reasons (Barrett et al, 2016;Fitzgerald & Townsend, 2012;Francis et al, 2016;Hegney et al, 2015;Stewart et al, 2020).…”
Section: What Does This Paper Contribute To the Wider Global Clinical...mentioning
confidence: 99%